Pemodelan Molekul, Sintesis dan Penentuan Aktivitas Antineoplastik 1-(4-Trifluorometilbenzoiloksi)Urea - SUKO HARDJONO (JURNAL ILMU KEFARMASIAN INDONESIA, 2016)
To design new drugs, physical-chemical characteristics of drug molecules can be predicted by in silico test before drugs are synthesized. Ribonucleotide reductase is the main target or receptor of antineoplastic compounds such as hydroxyurea (HU) and its derivatives like 1-(4-trifluoromethylbenzoyloxy)urea or 4-CF3BOU. This compound forms a complex with crystal structure of ribonucleotide reductase I enzyme, which is 2EUD. The hydrogen bond and bond energy in the form of rerank score from both complexes was calculated with Molegro program. Theoretically, compound activity is indicated by rerank score. The compound whose rerank score is small is predicted to have greater activity. The activity of 4-CF3BOU was found to be greater than HU. The reaction mechanism of synthesis 4-CF3BOU was the substitution of nucleophilic hydroxyl group from HU to carbonyl group of 4–trifluoromethylbenzoyl chloride (4-CF3BCl). Purity test was conducted using TLC and melting point. Structure identification was performed based on the spectra of UV-VIS, FT-IR, H/C-NMR and MS. In this study, 4-CF3BOU was discovered to have antineoplastic activity with the IC50 value of 82.37 μg/mL and was tested towards HeLa cells. On the other hand, HU had the IC50 value of 430.21 μg/mL. The antineoplastic activity of 4-CF3BOU was greater than HU.